Music Preferences of Teenage Students in Relation to Listener Psychology and Environmental Influences - Yeoh, Miranda Poh Khoon (2002)
A survey was carried out to investigate music preferences of 436 teenage students from the four pilot schools offering music education in the Klang valley. Respondents were selected by random cluster sampling. Twenty-four brief music excerpts, six each of ethnic-related Malaysian music, pop, rock and western art music were utilised. Besides studying the whole sample, music preferences of KBSM Music students (n = 205) were compared to those of non-music students (n = 231). KBSM Music students obtained higher preference means for most of the excerpts, especially instrumental ones as compared to the non-music students. Music students also had higher preference means for all the four genres under study. Correlation analyses showed that three independent variables ('Familiarity', 'Influence of Mood', a psychological variable and 'Influence of Music Characteristics') with consistent moderate correlations with Music Preference and with preferences for all the genres for the whole sample and both subject option sub-samples. However, only the music sub-sample showed moderate correlations for the influence of other variables (Family, Peers, Teachers, Artistes/ Composers, Media and Incidental Conditioning) on western act music preference. For non-music students only, the psychological variable 'Wellness of Mood' showed a low but significant correlation with Music Preference, and preferences for the commercial genres, pop and rock. Only for non-music students, the personality dimensions 'Neuroticism', and 'Extraversion' showed low but significant correlations preference for commercial music.